2011
DOI: 10.1539/joh.o10031
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Receiving a Workplace Oral Health Examination Including Oral Health Instruction and Oral Health Status in the Japanese Adult Population

Abstract: Relationship between Receiving a Workplace Oral Health Examination Including Oral Health Instruction and Oral Health Status in the Japanese Adult Population: Tadaaki Oshikohji, et al. Section of Preventive and Public Health Dentistry, Division of Oral Health, Growth and Development, Kyushu University Faculty of Dental Science— Objectives Dental caries and periodontal disease are highly prevalent in the Japanese adult population. Oral examination is an effective method to ind various oral health problems in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…We believe that improving management of working hours and reducing the amount of overtime work are important factors for promoting preventive dental visits, which play a vital role in oral health. In addition to reducing overtime hours, it is important to consider other options, such as conducting dental examinations in workplace settings [25] or allowing workers to visit dental clinics during working hours, particularly younger workers and male workers aged over 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that improving management of working hours and reducing the amount of overtime work are important factors for promoting preventive dental visits, which play a vital role in oral health. In addition to reducing overtime hours, it is important to consider other options, such as conducting dental examinations in workplace settings [25] or allowing workers to visit dental clinics during working hours, particularly younger workers and male workers aged over 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Pizzatto 60 observed that availability of dental care in the workplace facilitates access to employees, reduces the time away from the production line and fosters integration among workplace health and safety professionals, while knowledge of the work routine and production process helps dentists to establish a more accurate diagnosis and health promotion and prevention actions better adjusted to the local conditions. In a study from 2011 with 15,338 workers, Oshikohji et al 61 found that the rates of oral diseases and tooth loss were lower among those who had received systematic oral primary health care in the workplace, including orientation on hygiene and periodical consultations, by comparison to the employees who had received only eventual or no care at all. While some authors reported that oral health prevention programs are associated with reduction of costs 62 , 63 , thorough studies on return (ROI) and value (VOI) on investment are still missing in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Actions to improve the quality of life of workers as concerns their oral health may be enhanced by means public health policies focusing on prevention, including continuing education, extending the operating hours of services beyond the working time of workers, implementing measures already established in legislation, such as removal of bureaucratic barriers, and reducing costs to employers to promote general and oral health care. Incentives may be afforded to private organizations to participate in health education programs, provide dental care to employees or even better, to establish facilities on their premises 26 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Menegaz et al suggested that a follow-up time of less than one year led to a lack of efficacy for educational intervention [23]. In addition, Oshikohji et al reported that workers who had more participation time for oral examination and oral health instruction had better periodontal condition than those with less time [24]. If the duration of this study and/or the frequency of instruction was increased, oral health status might improve.…”
Section: Discussionmentioning
confidence: 99%